The approaches and prospects for natural organic matter-derived disinfection byproducts control by carbon-based materials in water disinfection progresses. (15th August 2021) - Yang, Hailan; Ye, Shujing; Wang, Jiajia; Wang, Han; Wang, Ziwei; Chen, Qiang; Wang, Wenjun; Xiang, Ling; Zeng, Guangming; Tan, Xiaofei
Abstract: The formation of unintended disinfection by-products (DBPs) mainly results from the reaction between the widespread natural organic matter (NOM) and disinfectants in source water and wastewater disinfection progresses. Although waterborne diseases are controlled by disinfection, the generated DBPs show a high risk to human health accompanying disinfection, and receive considerable attention. Carbon materials are widely used in different stages of water treatment progress. They show good adsorption and catalytic performance, and the low price makes them competitive in engineering application. Moreover, carbon materials show high ability in decreasing the concentration of NOM, intermediates of NOM-derived DBPs and DBPs themselves during the different stages of water treatment. This review aims to highlight the removal of NOM and NOM-derived DBPs through the application of carbon materials, and to explain the conversion and potential risks of NOM in water disinfection. The operating forms of different carbon materials including adsorbents, filling materials of membrane and catalysts of advance oxidation progresses (AOPs) are summarized systematically. Moreover, new DBP precursors introduced by the application of carbon materials are discussed. Lastly, perspectives on the challenges for DBPs control in emerging conditions such as stormwater reuse, microplastics pollution, or water treatment of public health emergency, are proposed for further development. Graphical abstract: Image 1